Wing morphology of the active flyer Calliphora vicina (Diptera: Calliphoridae) during its invasion of a sub‐Antarctic archipelago where insect flightlessness is the rule. (2nd May 2016) - Laparie, Mathieu; Vernon, Philippe; Cozic, Yann; Frenot, Yves; Renault, David; Debat, Vincent
Abstract : The cosmopolitan blowfly Calliphora vicina became established in the sub‐Antarctic Kerguelen Islands in the late 1970s, following a warming period that allowed its full development. Although temperature and wind may limit flight activity, the fly invaded the archipelago, reaching sites remote from the introduction point. Most native competitors have converged to flightlessness as a response to stringent environmental conditions and therefore the flight strategy of C. vicina might be either a handicap or a competitive advantage under ongoing climate change. Using geometric morphometrics, we investigated whether the wing had changed over time in C. vicina within the archipelago (1998 vs. 2009) and compared its morphology with that of a continental population from a temperate area (1983 vs. 2009). Wing shape plasticity to temperature was also experimentally investigated. We found no clues of relaxed selection on flight morphology in the range invaded. However, rapid changes of wing shape occurred over time in females from the Kerguelen Islands compared with both males and females of the continental population, despite a shorter time‐lag between samples in the former. The thermal reaction norms for wing shape found for C. vicina from Kerguelen were also different from those of the continental population, but it remains unknown whether this resulted from or preceded the introduction. These combined findings are consistent with a fingerprint of local adaptation in the invasive population. However, the adaptive significance of the changes, in terms of their aerodynamic consequences and the future evolution of C. vicina in the Kerguelen Islands, requires further investigation. From an evolutionary standpoint, sustaining flight capability under the novel sub‐Antarctic conditions might be critical to the invasive success of C. vicina as most competitors are flightless.